Math, asked by shemalpreet17, 5 months ago

(a²)³ answer this question ​

Answers

Answered by ravibharsing
1

Answer:

(a²)³

(a²)³

Answered by pulakmath007
3

\displaystyle \sf   {( {a}^{2} )}^{3}  =    {a}^{6}

Given :

The expression (a²)³

To find :

Simplify the expression

Solution :

Step 1 of 2 :

Write down the given expression

Here the given expression is (a²)³

Step 2 of 2 :

Simplify the given expression

We are aware of the formula on indices that

 \displaystyle \sf{ { ({a}^{m} )}^{n} =  {a}^{mn}  }

Taking m = 2 , n = 3 we get

 \displaystyle \sf{ { ({a}^{2} )}^{3} =  {a}^{(2 \times 3) }  }

\displaystyle \sf{ \implies }{( {a}^{2} )}^{3}  =    {a}^{6}

 \boxed{ \:  \sf {( {a}^{2} )}^{3}  =    {a}^{6}  \:  \: }

━━━━━━━━━━━━━━━━

Learn more from Brainly :-

1. choose the correct alternative : 100¹⁰⁰ is equal to (a) 2¹⁰⁰ × 50¹⁰⁰ (b) 2¹⁰⁰ + 50¹⁰⁰ (c) 2² × 50⁵⁰ (d) 2² + 50⁵⁰

https://brainly.in/question/47883149

2. Using law of exponents, simplify (5²)³÷5³

https://brainly.in/question/36250730

#SPJ3

Similar questions